Bridging Fiqh and Religious Practice: Actualizing the Function of Ḥāshiyah as a Form of Worship in the Scribal Traditions of Madurese Pesantren Literature - Cholily, Naufal; Ghozali, Mahbub; Kholid, Abd.; Wan Mokhtar, Wan Khairul Aiman; Mahmut, Rami İbrahim (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
The function of the ḥāshiyah (gloss), traditionally serving as an explanatory tool for words requiring further exploration, underwent a transformation in its application by kiai (local religious leader) in the pesantren (Islamic boarding school) of Madura. This shift arose from the need to actualize meanings and reinforce worship practices rooted in the Shāfi‘ī school of jurisprudence (madhhab). The emphasis on the Shāfi‘ī school was driven by the religious dynamics of 19th-century Madurese society, which leaned heavily toward mystical practices and tarekat (spiritual path) traditions. This study aims to identify the scribal process and glosses in the fiqh (Islamic jurisprudence) literature of Madurese pesantren and their connection to efforts to shape a new religious practice among Madurese people. A qualitative method, informed by social construction theory, was employed to guide the analysis of the data. This study found that the preferences and choices of specific Shāfi‘ī jurisprudence literature closely align with the literature commonly used in pesantren throughout Indonesia. This shared selection reflects the recognition of Madurese kiai and become an objective reality widely accepted as standard educational material in pesantren. In response to this objective reality, Madurese kiai incorporated additional explanations that not only elucidate meanings but also address questions about the religious practices of the Madurese people, which often gravitated towards tarekat connections and mystical traditions. These commentaries extend beyond simple linguistic clarification, challenging Islamic behaviors that deviate from fiqh logic. They serve as a transformative force within the Islamic tradition, facilitating the emergence of new religious practices and reinforcing the evolving function of commentary as a means of shaping and influencing religious behavior. [Peralihan fungsi ḥāshiyah, sebagai komponen penjelas kata-kata yang membutuhkan eksplanasi, mengalami pergeseran dalam proses produksinya oleh para kiai pesantren di Madura. Peralihan ini didasarkan pada kebutuhan aktualisasi makna untuk menguatkan praktik ibadah yang berdasarkan fikih mazhab Shāfi‘ī. Kebutuhan penekanan atas mazhab Shāfi‘ī didasarkan pada dinamika keagamaan masyarakat Madura abad ke-19 Masehi yang cenderung bertendensi pada praktik mistis dan pengamalan tarekat. Penelitian ini bertujuan untuk menemukan proses dialektis antara kiai yang berdialektika dengan literatur fikih yang menjadi teks sumber dengan realitas sosial-keagamaan dalam proses pembentukan struktur dan tindakan hukum masyarakat Madura. Penelitian ini menggunakan metode kualitatif dengan alat analisis teori konstruksi sosial untuk menangkap proses penyalinan dan komentar yang berlangsung di dua pesantren tua di Madura. Penelitian ini menemukan bahwa teks-teks sumber yang disalin memiliki keidentikan dengan teks-teks yang dipelajari oleh pesantren-pesantren di wilayah Indonesia pada umumnya dengan tendensi kecenderungan penuh terhadap mazhab Shāfi‘ī. Struktur identik dalam pemilihan literatur menunjukkan literatur mazhab Shāfi‘ī sebagai realitas objektif yang diterima oleh seluruh pesantren sebagai bahan pengajaran. Meskipun literatur tersebut merupakan kesepakatan umum, para kiai memberikan respons makna yang bersifat subjektif dengan membawa seperangkat pengetahuan kognitif melalui penjelasan atas kosa-kata tertentu dengan mengambil teks-teks lain yang tidak ditemukan salinan materialnya. Penjelasan atas konsep kata tidak hanya berorientasi pada pemahaman makna, akan tetapi memuat refleksi kegelisahan terhadap realitas keagamaan masyarakat Madura yang cenderung berafiliasi dengan tarekat dan praktik-praktik mistik lainnya. Kritik atas tindakan keagamaan yang tidak sesuai dengan nalar fikih menunjukkan perluasan fungsi dari komentar dalam tradisi Islam sebagai komponen pembentukan tindakan keagamaan baru.]